2014
DOI: 10.1111/apt.12884
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: polyethylene glycol 3350 with sports drink vs. polyethylene glycol with electrolyte solution as purgatives for colonoscopy – the incidence of hyponatraemia

Abstract: SUMMARY BackgroundPolyethylene glycol 3350 plus sports drink (PEG-SD) is a hypo-osmotic purgative commonly used for colonoscopy, though little safety data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The prevalence of hyponatraemia following polyethylene glycol has been recently established in a clinical trial where 3.9% of patients developed hyponatraemia. 29 Although the need for hospitalization in this situation is thought to be small, several serious adverse events with seizures and coma have been reported. 30 Patients preparing for colonoscopy are generally told to increase the amount of oral fluids prior to colonoscopy and the stomach or bowel distension is likely to produce non-osmotic ADH release predisposing to severe hyponatraemia.…”
Section: Hyponatraemia In the Preoperative Evaluationmentioning
confidence: 99%
“…The prevalence of hyponatraemia following polyethylene glycol has been recently established in a clinical trial where 3.9% of patients developed hyponatraemia. 29 Although the need for hospitalization in this situation is thought to be small, several serious adverse events with seizures and coma have been reported. 30 Patients preparing for colonoscopy are generally told to increase the amount of oral fluids prior to colonoscopy and the stomach or bowel distension is likely to produce non-osmotic ADH release predisposing to severe hyponatraemia.…”
Section: Hyponatraemia In the Preoperative Evaluationmentioning
confidence: 99%
“…Table summarises RCTs that included PEG‐ELS or PEG‐SD arms and report the incidence of hyponatraemia . While individual serum sodium levels are not detailed, no instances of symptomatic hyponatraemia were observed in these 1695 subjects.…”
Section: Randomised Controlled Trials With Peg‐els or Peg‐sd That Repmentioning
confidence: 99%
“…In addition, significantly more patients with low serum sodium had diabetes and a greater proportion had hypertension, cardiovascular disease or liver disease. 2 While this study adds to the current literature the identification of risk factors for development of asymptomatic hyponatremia, it was not powered to detect the incidence of severe symptomatic hyponatremia, which can occur after different PEG formulations. Indeed, over the past years, nine cases of severe, symptomatic, hypotonic hyponatremia have been reported (Table 1), [3][4][5][6][7][8] one of which had a fatal outcome.…”
mentioning
confidence: 98%
“…A systematic review of safety issues associated with bowel cleansing concluded that, with formulations containing polyethylene glycol and electrolytes (PEG-ELS), adverse events are uncommon, but potentially serious. 1 In a recent issue of Alimentary Pharmacology & Therapeutics, Matro et al 2 added another piece to puzzle. They performed a RCT, comparing PEG 3350 plus sport drink (PEG-SD) with PEG-ELS, specifically designed to evaluate safety measures, with the incidence of hyponatremia as primary end-point.…”
mentioning
confidence: 99%
See 1 more Smart Citation